Donepezil alone and combined with intensive language-action therapy on depression and apathy in chronic post-stroke aphasia: A feasibility study - Berthier-Torres, Marcelo Luis; Edelkraut, Lisa; López-González, Francisco Javier; López-Barroso, Diana; Mohr, Bettina; Pulvermüller, Friedemann; Starkstein, Sergio E.; Jorge, Ricardo E.; Torres-Prioris, María José; Dávila-Arias, María Guadalupe (Elsevier, 2022)
This study explored the feasibility and effectiveness of a short-term (10-week) intervention trial using Donepezil administered alone and combined with intensive language action therapy (ILAT) for the treatment of apathy and depression in ten people with chronic post-stroke aphasia. Outcome measures were the Western Aphasia Battery and the Stroke Aphasia Depression Questionnaire-21. Structural magnetic resonance imaging and 18fluorodeoxyglucose positron emission tomography were acquired at baseline and after two endpoints (Donepezil alone and Donepezil-ILAT). The intervention was found to be feasible to implement. Large treatment effects were found. Donepezil alone and combined with ILAT reduced aphasia severity, while apathy and depression only improved with Donepezil-ILAT. Structural and functional neuroimaging data did not show conclusive results but provide hints for future research. Given these overall positive findings on feasibility, language and behavioral benefits, further studies in larger sample sizes and including a placebo-control group are indicated.
Keywords: Afasia; Apatia; Logopedia; Neurobiología; Neuropsicofarmacología; Enfermedad cerebrovascular -- Tratamiento; Enfermedad cerebrovascular -- Pacientes -- Rehabilitación; Aphasia; Apathy; Depression; Donepezil; Intensive language-action therapy; Neuromaging; Pharmacotherapy; Stroke